Differential Impacts of Acute, Chronic, and Social Defeat Stress on Microglial Morphology in the Amygdala and Habenula - Zea-Doña, Alejandro; Nieto-Quero, Andrea; Infantes-López, M. Inmaculada; Arjona, A.; Tabbai-Amal, Sara; Zambrana-Infantes, Emma; Chaves-Peña, Patricia; Muñoz-Martín, José; Martín-Aguiar, Víctor; Blanca-Mena, María José; Pérez-Martín, Margarita; Pedraza-Benítez, María del Carmen (My University, 2025)
Stress is a major risk factor for neuropsychiatric disorders, including depression and post-traumatic stress disorder (PTSD), which disrupt emotional regulation and cognitive function. Microglia, the brain’s resident immune cells, play a critical role in maintaining neural homeostasis by modulating synaptic plasticity and responding to environmental challenges. Their morphological changes, such as alterations in soma size, density, and circularity, reflect distinct neuroimmune responses to stress. This study focuses on the basolateral (BLA) and central (CeA) amygdala, key for emotional processing, and the lateral (LHb) and medial (MHb) habenula, involved in motivation and reward. Understanding region-specific microglial adaptations to acute, chronic, and social defeat stress may help uncover mechanisms underlying stress vulnerability.
Keywords: Microglia; Núcleo amigdalino; Neuropsiquiatría; Estrés (Fisiología); Microglial morphology; Amygdala; Habenula